IKZF1 exacerbates the inflammatory response by epigenetically modulating mitochondrial function following acute peritonitis - Liu, Guanya; Hu, Pengfei; Dong, Ying; Xu, Yamin; Yang, Zhengyao; Qi, Zihao; Su, Yuantao (Frontiers in Immunology, 2025)
BackgroundMacrophages play pivotal roles in immune homeostasis and host defense against pathogens, yet their excessive activation can lead to tissue damage. Acute peritonitis induced by cecal ligation and puncture (CLP) is associated with dysregulated macrophage-mediated inflammation. IKZF1, a transcription factor, has been implicated in immune regulation, but its role in CLP-induced macrophage activation remains unclear. This study aimed to investigate the molecular mechanism of IKZF1 in regulating inflammatory responses during acute peritonitis.MethodUsing a murine CLP-induced peritonitis model, we analyzed IKZF1 expression in macrophages via RT-qPCR and western blot. Lenalidomide (Len), an IKZF1 inhibitor, was administered to assess its effects on macrophage inflammation and lung injury. Mitochondrial function was evaluated by measuring reactive oxygen species (ROS), ATP levels, and succinate accumulation. Mechanistic studies included chromatin immunoprecipitation (ChIP), co-immunoprecipitation (Co-IP), and HDAC3 activity assays. SDHB expression and acetylation status were analyzed under LPS stimulation, with acetate supplementation used to modulate histone H3K9 acetylation.ResultsIKZF1 expression was significantly upregulated in macrophages during CLP-induced peritonitis. Len treatment suppressed IKZF1, attenuating inflammatory responses and mitigating lung injury. Mechanistically, IKZF1 directly repressed SDHB expression by recruiting HDAC3 to deacetylate SDHB, leading to mitochondrial dysfunction and amplified inflammation. Supplementation with acetate restored H3K9ac levels at the SDHB promoter, counteracting LPS-induced suppression of SDHB. These findings highlight an IKZF1/HDAC3-SDHB-succinate axis driving macrophage hyperactivation.ConclusionIKZF1 exacerbates macrophage inflammation in CLP-induced peritonitis by epigenetically silencing SDHB via HDAC3-mediated deacetylation, thereby disrupting mitochondrial metabolism and amplifying pro-inflammatory signals. Targeting IKZF1 or enhancing acetylation may represent novel therapeutic strategies for acute inflammatory conditions. This study establishes IKZF1 as a potential biomarker and therapeutic target for mitigating excessive inflammation in peritonitis.